Mode analysis and characterization of photonic crystal fibers - Tan, Zhi Hao. (2010)
Photonic crystal fibers (PCFs) are a new class of optical fibers based on the properties of photonic crystals. The presence of air-holes in these fibers enabled them to confine light in hollow cores and also confinement characteristics that is not possible in conventional optical fibers, and their optical properties being greatly influenced by the geometric parameters. They may also be known as microstructured optical fibers, holey fiber or photonic-bandgap fibers. The continuing development of optical components required them to be developed on an ever-smaller scale [9]. In order to characterize them, various techniques have been developed. One of such technique is the scanning near-field optical microscopy (SNOM), where it overcomes the diffraction limitation of conventional optical microscopy technique and able to capture optical images at nanometric scale. In this project, this technique will be applied on PCF samples, of different microstructures, to capture and to analyze their fundamental mode profile intensity in the near-field region. Two types of measurement mode will be studied to evaluate the feasibility and resolution of this technique. The technique of near-field acquisition of optical images will be critical in characterization for nano-photonic device applications.